FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR - ELIZABETH HANNA; FRISKA FIRNANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this research is to obtain empirical evidence of audit structure, role conflict, good governance comprehension, organization culture, leadership style have affect to auditor performance. Subject in this research are auditors who work at public accounting firm in Jakarta. The sample is selected using purposive sampling method. Number of questionnaires distributed was 199 copies, but only 122 questionnaires returned and meet the criteria to use as samples for this research. This research uses multiple regressions. The result of this research shows that audit structure, role ambiguity, organization culture, and leadership style affect the auditor performance, but role conflict, organization commitment and good governance comprehension do not affect the auditor performance.